Soil solarization as a non-chemical weed control method in tree nursery production systems of the Pacific Northwest, USA - Wada, Nami; Berry, Pete A.; Hill, Brian; Mallory-Smith, Carol; Parke, Jennifer L. (Frontiers in Agronomy, 2024)
Introduction Herbicide application in tree nurseries is limited because of the potential for chemical injury to the large diversity of trees species grown, the lack of registered products, and increasing restrictions on herbicide use, necessitating the costly practice of hand weeding. Soil solarization can reduce the weed seedbank by trapping solar energy under clear plastic film, resulting in high soil temperatures lethal to imbibed weed seeds and seedlings. The objective of this study was to determine if soil solarization would be an effective weed management strategy in Pacific Northwest, USA, tree production systems. Methods Field studies were conducted at three commercial tree nurseries in Oregon and Washington over two years to test soil solarization in reducing the naturally occurring weed seedbank and the time required to hand weed fields. Further field and laboratory tests were conducted with five weed species: Poa annua, Polygonum pensylvanicum, Amaranthus retroflexus, Portulaca oleracea, and Cyperus esculentus. Weed seeds and tubers were buried in packets at 5 and 10 cm to determine their viability after 6 weeks of solarization. A laboratory study was conducted with all but C. esculentus to quantify the exposure time at 45, 50, and 55°C required for 90% death (T90). Results Soil solarization was particularly effective in reducing the emergence of naturally occurring weeds in the fall and winter, when weed emergence was reduced by 94-96%. Emergence was reduced 67-81% during the subsequent spring and early summer. Nine to ten months after solarization, solarized areas had a 52 – 69% reduction in hand weeding time compared to non-solarized areas. In field trials with buried seed and tuber packets, mortality differed by location and depth, with P. annua and P. pensylvanicum having the greatest percent seed mortality followed by A. retroflexus and variable results for P. oleracea and C. esculentus. In lab studies, seed mortality differed depending on species and temperature; however, at 55°C, there was a relatively rapid drop in seed viability for all species, and T90 values ranged from 1.2 to 41 h whereas at 45°C the range was 47 to > 3000 h. Similar to the field studies, P. annua and P. pensylvancium were more sensitive to heat, followed by A. retroflexus and P. oleracea. Conclusion Soil solarization can be an effective weed management tool in reducing the weed seedbank in Pacific Northwest tree nurseries and other fall-sown crops but may not work for certain, thermotolerant weed species such as C. esculentus.